Wake and Mourning: Apollinaire and Ungaretti (AmeriQuests, 2015)
The Great War is the first modern war in which a great awareness of the double role soldiers played was elaborated, as many of those soldiers were also writers and artists who kept on working on their artistic endeavor while at war. Among them, there were certainly poets who immediately earned the compound title of soldier-poets, according to an order of the two terms that remarked the priority of the urgency of the contingencies of war: they were soldier-poets rather than poet-soldiers. To be sure, the definition of poet-soldier gained some popularity during the Romantic period and the Italian Risorgimento, in particular: one may think of poet-soldiers such as Ugo Foscolo, but also Lord George Byron. Even during World War I there was a poet-soldier of the caliber of Gabriele D’Annunzio. However, it is during the Great War that the compound title of poet-soldier is reversed into soldier-poet. Furthermore, another broader distinction was elaborated: that between combatant and non-combatant. It is this distinction, in conjunction of that within the compound title of soldier-poet, which proves to be crucial in order to read some war poems by Guillaume Apollinaire and Giuseppe Ungaretti as telling in regards to the attitude the soldier-poet had to take before his role as combatant or non-combatant.